Adaptasi Alat Ukur Professional Quality of Life pada Psikolog Klinis di Fasilitas Kesehatan - Nabila Ghassani Putri; Fredrick Dermawan Purba; Yuliana Hanami (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Professional Quality of Life (PROQOL) is the quality one feels in relation to their work as a helper. Both the positive and negative aspects of doing the job influence ones professional quality of life. People who work in helping professions may respond to individual, community, national, and even international crises. PROQOL-V has been widely researched in Indonesia despite the limitation of its measurement tool and its usage on clinical psychologist subjects. Therefore, it is deemed necessary to adapt PROQOL measurement as a research tool for clinical psychologist in Indonesia. This study aims to adapt the Indonesian version of the PROQOL-V measurement by ensuring that the instrument has good measurements characteristics, namely validity and reliability. This study uses quantitative research. The instrument PROQOL-V consisting of 30 items that was administered to 100 professional clinical psychologist. The evidence of validity was acquired from expert judgment when designing the instrument and Pearson correlation.The reliability was tested using Cronbsch's Alpha coefficient (α). The item analysis found that the Pearson correlation values ranged from 0.214 to 0.718 with r table pearson product moment 0.195, and reliability testing resulted a value of α = 0.692. It can be concluded that the Indonesian version of the PROQOL-V instrument usage on clinical psychologist subjects is valid and reliable.